Types of Self-Efficacy in Youth Physical Activities: Tipe Efikasi Diri dalam Aktivitas Jasmani Remaja - Diky Hadyansah (Journal of Physical and Outdoor Education, 2021)
This study aims to determine the absence of activities that contribute to the type of self-efficacy on adolescent physicality. The method used is descriptive correlational method. The subjects of this study were 241 students of high school (SMA) class in Bandung City. Determination of the sample using cluster rondom sampling technique. The data collector used a survey through a questionnaire and a scale. The instruments used in the study consisted of two instruments, namely: the exercise self-efficacy scale, while the instruments used in measuring physical activity and adapting the Physical Activity Questionnaire for Adolescents (PAQA) instrument. The data analysis technique used is to perform multiple linear regression analysis. The results showed that self-efficacy contributed 33% to the physical activity of adolescents. While the partial amount is 27% for Task Efficacy, 29% for Coping Efficacy and 26% for Scheduling Efficacy.